Low Thermal Resistance of Diamond‐AlGaN Interfaces Achieved Using Carbide Interlayers - Henry T. Aller; Thomas W. Pfeifer; Abdullah Mamun; Kenny Huynh; Marko Tadjer; Tatyana Feygelson; Karl Hobart; Travis Anderson; Bradford Pate; Alan Jacobs; James Spencer Lundh; Mark Goorsky; et al. (Advanced Materials Interfaces)
Abstract This study investigates thermal transport across nanocrystalline diamond/AlGaN (aluminum gallium nitride) interfaces, crucial for enhancing thermal management in AlGaN‐based electronic devices. Chemical vapor deposition growth of diamond directly on AlGaN resulted in a disordered interface with a high thermal boundary resistance (TBR) of 20.6 m2‐KGW−1. Sputtered carbide interlayers of boron carbide (B4C), silicon carbide (SiC), and a mixture of boron carbide and silicon carbide (B4C/SiC) are employed to reduce thermal boundary resistance in diamond/AlGaN interfaces. The carbide interlayers resulted in record‐low thermal boundary resistance values of 3.4 and 3.7 m2‐KGW−1 for Al0.65Ga0.35N samples with B4C and SiC interlayers, respectively. STEM imaging of the interface reveals interlayer thicknesses between 1.7 and 2.5 nm, with an amorphous structure. Additionally, Fast‐Fourier Transform (FFT) characterization of sections of the STEM images displayed sharp crystalline fringes in the AlGaN layer, confirming it is properly protected from damage from hydrogen plasma during the diamond growth. In order to accurately measure the thermal boundary resistance we develop a hybrid technique, combining time‐domain thermoreflectance and steady‐state thermoreflectance fitting, offering superior sensitivity to buried thermal resistances. The findings underscore the efficacy of interlayer engineering in enhancing thermal transport and demonstrate the importance of innovative measurement techniques in accurately characterizing complex thermal interfaces. This study provides a foundation for future research in improving thermal properties of semiconductor devices through interface engineering and advanced measurement methodologies.